Applications of the principles fo Godhood an undergraduate thesis on poetry writing. - Paulino, Mark Jaesen C.
The tools of the writer of poetry enable him to generate a feasible reality for the reader be drawn into and, ultimately acknowledge. This writer's "poetics" or guidelines for poetry writing concentrate on acceptable surreality and manipulaton of form. A third, unifying principle is the focus on imagination. The twenty poems presented in this collection are constructed with these principles., This writer discusses the poems under these headings: Language and Poetics, and Thematic influences. Each heading constitutes a cluster of subtopics. "Language and Poetics" discusses the way this writer manipulates the English language delineates the various literary tools he employed in writing, such as the economy of words, the avoidance of highfalutin language, and the use of direct quotations, followed by a brief comparison among the poetry of e. e. cummings, the lyrics of John Mayer, and this writer's own poetry. "Thematic Influences" discusses the various thematic influences that this writer drew from in the creation of his poetry. The importance of the god motif is emphasized and then used as a springboard to the discussion of this writer's thematic influences, ranging from the graphic novels of Alan Moore and Neil Gaiman to the roleplaying game "Nobilis" by Jenna Katerin Moran. Mainly, this chapter discusses the typical world that this writer creates and notes the similarities present in the worlds created by Moore, Gaiman, and Moran.